استراتيجيات التعلّم النّشط وأثرها في تحصيل القواعد النحوية واتجاهات الطلبة نحوها للصف الثامن في مدينة أبو ظبي - أحمد عبد الرحمن القاسم; Ahmad Abdulrahman Al-Kasem (Universiti Sains Islam Malaysia, 2026)
Grammar forms the cornerstone of mastering and understanding the Arabic language. However, previous studies have revealed a noticeable decline in students’ academic achievement in grammar, along with their aversion to learning it. The core problem addressed in this study lies in the weak student engagement in grammar lessons and their low academic performance, which necessitates the adoption of modern, alternative instructional strategies that enhance learning motivation and improve academic outcomes.Accordingly, this study aimed to investigate the impact of active learning strategies on improving students’ achievement in Arabic grammar and on developing positive attitudes toward the subject. It also sought to examine whether there are statistically significant differences in achievement and attitudes attributable to gender.This study uncovered the significant impact of active learning strategies on enhancing eighth-grade students' academic achievement in grammar and cultivating positive attitudes toward the subject. Additionally, the study explored whether gender plays a role in influencing students’ achievement and attitudes.To address these questions, the study adopted both the descriptive analytical approach to examine and interpret the phenomenon, and the quasi-experimental approach to compare the outcomes of two groups: an experimental group taught using active learning strategies, and a control group taught through traditional methods. A variety of research instruments were used, including a teacher’s guide, a student’s textbook, a pre- and post-achievement test, an attitude-measuring questionnaire, and interviews with teachers. The study was applied to a sample of eighth-grade students in public schools in Abu Dhabi. Statistical analyses were conducted using appropriate tools such as Cronbach's Alpha to test the reliability of the questionnaire, means and standard deviations to assess performance on the achievement tests, the T-test to measure differences between group means, and ANCOVA to determine the significance of differences between the two groups.The findings revealed a statistically significant positive impact of active learning strategies on improving the academic achievement of students in the experimental group compared to the control group. The study also found that these strategies contributed to the development of positive student attitudes toward grammar. Moreover, no statistically significant differences were found in achievement or attitudes based on gender.The study recommends the integration of active learning